Sosialisasi dan Promosi Program Studi Teknik Perangkat Lunak-Universitas Universal - Holong Marisi Simalango (STIT Al - Ibrohimy Bangkalan, 2024)
Education is important in shaping quality generation. From kindergarten to college, the college must conduct research, devotion, and education, and create quality students. College forms entrepreneurs, human resources, and economic growth. Socialization and promotion by training students in Bodhi Dharma High School in Batam City. Participants are students from the tenth grade (X), eleven (XI), and twelve (XII). The results of the implementation of this activity indicate that socialization and promotion through training can provide complete and clear information about the Software Engineering study program. Information disseminated becomes a reference in considering where to continue education at Universal University.